2008
DOI: 10.1016/j.cellsig.2008.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Morphine-induced μ-opioid receptor rapid desensitization is independent of receptor phosphorylation and β-arrestins

Abstract: Receptor desensitization involving receptor phosphorylation and subsequent βArrestin (βArr) recruitment has been implicated in the tolerance development mediated by μ-opioid receptor (OPRM1). However, the roles of receptor phosphorylation and βArr on morphine-induced OPRM1 desensitization remain to be demonstrated. Using OPRM1-induced intracellular Ca 2+ ([Ca 2+ ] i ) release to monitor receptor activation, as predicted, [D-Ala 2 , N-Me-Phe 4 , Gly 5 -ol]-enkephalin (DAMGO), induced OPRM1 desensitization in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 60 publications
4
63
1
Order By: Relevance
“…Our results show that, similarly to the MOP agonist DAMGO, the NPFF 2 agonist 1DMe induced the phosphorylation of the C-terminal tail of the human MOP receptor, in particular at a residue (Ser-377) known to play a key role in desensitization and internalization of the opioid receptor (35)(36)(37). This heterologous phosphorylation was specific to NPFF receptor activation because it did not occur when another G i/o -coupled receptor, the ␣ 2 -adrenergic receptor, was activated.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Our results show that, similarly to the MOP agonist DAMGO, the NPFF 2 agonist 1DMe induced the phosphorylation of the C-terminal tail of the human MOP receptor, in particular at a residue (Ser-377) known to play a key role in desensitization and internalization of the opioid receptor (35)(36)(37). This heterologous phosphorylation was specific to NPFF receptor activation because it did not occur when another G i/o -coupled receptor, the ␣ 2 -adrenergic receptor, was activated.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies have shown that Thr-370 and Ser-375 are the main targets of homologous regulation by G protein-coupled receptor kinases in the C-terminal tail of the rodent MOP receptor (35)(36)(37)(38), although a potential role for Thr-180 in the second intracellular loop has also been suggested in Xenopus oocytes (39). Here, we have studied the phosphorylation status of the human MOP receptor after homologous stimulation by its agonist (DAMGO) or after heterologous regulation by NPFF 2 receptors.…”
mentioning
confidence: 99%
“…FKBP12 Modulates the Morphine-Induced PKC« Activation and Recruitment. Morphine has been shown to increase the phosphorylation of OPRM1 at the Ser 375 residue only (Chu et al, 2008;Doll et al, 2011). Previous studies in our laboratory have shown that PKC« activation can be modulated by the phosphorylation state of the receptor (Zheng et al, 2008b;Chu et al, 2010).…”
Section: Fkbp12 and Morphine-induced Pkc« Activationmentioning
confidence: 95%
“…The relative densities of immunoprecipitated PKC« were quantified by normalizing to the total amount of immunoprecipitated receptors (D). *P , 0.05. shown to be PKC«-dependent (Chu et al, 2008(Chu et al, , 2010Zheng et al, 2008b). Thus, to further demonstrate that FKBP12 can modulate morphine-mediated PKC« activation, the influence of FKBP12 on ERK1/2 activation was investigated.…”
Section: Fkbp12 and Morphine-induced Pkc« Activationmentioning
confidence: 99%
“…Cholesterol concentrations were determined in the fi rst 10 fractions using an Amplex Red Cholesterol Assay Kit (Invitrogen, Carlsbad, CA). The amount of OPRM1 in the same fractions was determined by using [ 3 H] diprenorphine binding as described previously ( 18 ).…”
Section: Continuous Sucrose Gradientmentioning
confidence: 99%